Teori Keadilan Perspektif Gustav Radbruch: Hubungan Moral Dan Hukum - Al'anam, Muklis (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Gustav Radbruch's theory of justice places justice as the main pillar in the legal system. Radbruch emphasised that law cannot be separated from moral values and justice. In his perspective, an unjust law is not a true law. Radbruch identified three basic values of law: justice, legal certainty, and expediency. However, he asserted that justice should be the top priority.Radbruch experienced a change of view after World War II, where he realised that legal certainty should not come at the expense of justice. This research uses the normative method, which aims to examine legal norms. With conceptual and historical approaches. In conclusion, this article explores how Radbruch understood the concept of justice, how it interacts with other legal values, and its relevance in the modern legal context. Gustav Radbruch's theory of justice presents a dynamic interplay between moral and legal relationships, which primarily developed after his experiences with Nazi Germany. His legal philosophy, rooted in neo-Kantianism, grapples with the tension between legal positivism and natural law. Central to his thought is the ‘Radbruch formula,’ which states that grossly unjust laws have no legal validity.